The Introduction of Net-Platform-Centric Warfare in the Chinese Army (Pla) - Artsrun Hovhannisyan (Banber Arevelagitut'yan Instituti, 2025)
It is no surprise that just like the previous years, this year as well China has expanded its military budget, put another ship to sea, demonstrated new weaponary at the military parade, etc. For the last two decades, all the combat arms of the Chinese army has been developing at a high rate. Many authors claim very specific reasons for the Chinese armaments especially highlighting the conflicts with its immediate neighbors. From a geopolitical point of view, an interesting balance of power is being formed in the East. It’s been several years now that there are some precise problems in China-Japan conflict related to the power over some islands. China actively builds artificial islands which can serve as military bases far away from its shores approximately at an operative depth. And this matter deeply concerns the Philippines and Vietnam.